2016
DOI: 10.3758/s13414-016-1227-z
|View full text |Cite
|
Sign up to set email alerts
|

Bindings in working memory: The role of object-based attention

Abstract: Over the past decade, it has been debated whether retaining bindings in working memory (WM) requires more attention than retaining constituent features, focusing on domain-general attention and space-based attention. Recently, we proposed that retaining bindings in WM needs more object-based attention than retaining constituent features (Shen, Huang, & Gao, 2015, Journal of Experimental Psychology: Human Perception and Performance, doi: 10.1037/xhp0000018 ). However, only unitized visual bindings were examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(89 citation statements)
references
References 106 publications
8
79
2
Order By: Relevance
“…Using this approach, Allen, Baddeley, and Hitch () found that a concurrent backwards counting task or a verbal memory task impaired overall change detection performance, but did not have a selective impact on memory for feature bindings. These results were confirmed and extended in later studies with various concurrent tasks (Allen, Hitch, Mate, & Baddeley, ; Delvenne, Cleeremans, & Laloyaux, ; Morey & Bieler, ; Vergauwe, Langerock, & Barrouillet, ; Yeh, Yang, & Chiu, ) and were found to hold even when features were presented separately and had to be bound internally (Allen, Hitch, & Baddeley, ; Karlsen, Allen, Baddeley, & Hitch, ; but see Gao et al ., ). These results indicate that binding memory does not make specific demands on sustained attention (but see Brown & Brockmole, for a conflicting finding).…”
Section: Binding Features In Vwmmentioning
confidence: 97%
“…Using this approach, Allen, Baddeley, and Hitch () found that a concurrent backwards counting task or a verbal memory task impaired overall change detection performance, but did not have a selective impact on memory for feature bindings. These results were confirmed and extended in later studies with various concurrent tasks (Allen, Hitch, Mate, & Baddeley, ; Delvenne, Cleeremans, & Laloyaux, ; Morey & Bieler, ; Vergauwe, Langerock, & Barrouillet, ; Yeh, Yang, & Chiu, ) and were found to hold even when features were presented separately and had to be bound internally (Allen, Hitch, & Baddeley, ; Karlsen, Allen, Baddeley, & Hitch, ; but see Gao et al ., ). These results indicate that binding memory does not make specific demands on sustained attention (but see Brown & Brockmole, for a conflicting finding).…”
Section: Binding Features In Vwmmentioning
confidence: 97%
“…The passive view has been challenged by recent studies that have suggested that retaining bindings in WM is an active process requiring more object-based attention than retaining constituent features (Fougnie & Marois, 2009;Z. Gao et al, 2017;He, Li, Wu, Wan, Gao, & Shen, 2020;Lu, Ma, Zhao, Gao, & Shen, 2019;Shen et al, 2015).…”
Section: Does Retaining Binding Require More Attention Than Retainingmentioning
confidence: 99%
“…Specifically, we required the participants to memorize single features or bindings between them, and we then added a secondary task to the maintenance phase of WM to consume their object-based attention (Z. Gao et al, 2017;Lu et al, 2019;Shen et al, 2015). We predicted that a nonselective binding impairment would be observed; however, if a selective binding impairment emerged, that would imply that the previous selective binding impairment had just been an artifact of the testing procedure.…”
Section: Current Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhodes and colleagues argued for a distinction between binding of extrinsic features (i.e., linking of distinct items or contextual features accompanying an item) and binding of features that define the intrinsic characteristics of an object (i.e., within-item binding) (see also Allen et al, 2013; Rhodes et al, 2015). Binding objects' intrinsic features appears to be an automatic process (Allen et al, 2006, 2009; Karlsen et al, 2010; but see Shen et al, 2015; Gao et al, 2017) that is largely spared by age (Parra et al, 2009b; Brown and Brockmole, 2010; Isella et al, 2015; Rhodes et al, 2015; Read et al, 2016; Brown et al, 2017). In contrast, binding extrinsic features requires more cognitive resources (e.g., associative functions of the medial temporal lobe), which appear to be more susceptible to the effects of age (Mitchell et al, 2006).…”
Section: Introductionmentioning
confidence: 99%